Instructional Leadership of Principals on Students’ Achievement in Public Schools in Nepal - Adhikari, Narayan Prasad (Interdisciplinary Research in Education, 2022)
The purpose of this study is to find out the impact of principals' instructional leadership on students' achievement. School head teachers act as a leader and also a manager that determines students' achievements both directly and indirectly. Instructional leadership can significantly influence the quality of teaching and learning in the schools and consequently students' achievement, by improving the working conditions of the schools Literature shows that transformational leadership and instructional leadership determine the preferred styles of school improvement. This study shows that effective school leadership is the authority to lead the school. There is a growing understanding that leadership is surrounded in various organizational contexts within school communities, not centrally vested in a person or an office. The real challenge facing most schools is no longer how to improve but, more importantly, how to sustain improvement. Sustainability will depend upon the school’s internal capacity to maintain and support developmental work and sustaining improvement requires the leadership capability of the many rather than the few.